2019
DOI: 10.1088/1757-899x/534/1/012011
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of photoelectric converters intellectual system application on ground electric transport

Abstract: The development of environmentally friendly road transport is now directly related to the introduction of electric actuators, high-voltage storage systems and the accumulation of electricity in transport. Thus, a significant variety of hybrid traction drive circuits appears, which can be charged from an external power source. However, all of them use hydrocarbon fuel for charging and storage of electricity, which emits CO2 while burning. Clean electric vehicles are the most efficient in terms of environmental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…The results of mathematical modeling showed that in different latitudes of the Russian Federation the photovoltaic converters system may provide up to 260 kWh per year of electricity in the northern part of the country (at the latitude of St. Petersburg), up to 280 kWh per year in the central part of the country (at the latitude of Moscow), and up to 380 kWh in the southern part of the country (at the latitude of Sochi and Astrakhan). Taking into account CO2 emissions from electricity generation in the Russian Federation, it can be said that the use of this system in an electric vehicle will help to avoid unnecessary CO2 emissions in the amount of 153,000 to 240,000 grams per year [8] compared with an electric vehicle of a similar class with a standard method of charging [9]. The results of mathematical modeling showed that in different latitudes of the Russian Federation the photovoltaic converters system may provide up to 260 kWh per year of electricity in the northern part of the country (at the latitude of St. Petersburg), up to 280 kWh per year in the central part of the country (at the latitude of Moscow), and up to 380 kWh in the southern part of the country (at the latitude of Sochi and Astrakhan).…”
Section: Development Of the Electric Vehicle Energy Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of mathematical modeling showed that in different latitudes of the Russian Federation the photovoltaic converters system may provide up to 260 kWh per year of electricity in the northern part of the country (at the latitude of St. Petersburg), up to 280 kWh per year in the central part of the country (at the latitude of Moscow), and up to 380 kWh in the southern part of the country (at the latitude of Sochi and Astrakhan). Taking into account CO2 emissions from electricity generation in the Russian Federation, it can be said that the use of this system in an electric vehicle will help to avoid unnecessary CO2 emissions in the amount of 153,000 to 240,000 grams per year [8] compared with an electric vehicle of a similar class with a standard method of charging [9]. The results of mathematical modeling showed that in different latitudes of the Russian Federation the photovoltaic converters system may provide up to 260 kWh per year of electricity in the northern part of the country (at the latitude of St. Petersburg), up to 280 kWh per year in the central part of the country (at the latitude of Moscow), and up to 380 kWh in the southern part of the country (at the latitude of Sochi and Astrakhan).…”
Section: Development Of the Electric Vehicle Energy Systemmentioning
confidence: 99%
“…The WLTC cycle is generally less dynamic than ARTEMIS (mileage increased to 3.8%), but in the city cycle, it is not as favorable for the use of solar cells (up to 9.8%). In the second stage of work, according to the developed methodology, PHV elements with the most similar characteristics for battery manufacture were tested and selected [9]. The control units for operation of the temperature control system and the additional power supply system based on In the second stage of work, according to the developed methodology, PHV elements with the most similar characteristics for battery manufacture were tested and selected [9].…”
Section: Development Of the Electric Vehicle Energy Systemmentioning
confidence: 99%
See 1 more Smart Citation